OPTIMALISASI PENERAPAN KONSEP ANDRAGOGI DALAM PENDIDIKAN DAN LATIHAN APARATUR PEMERINTAH SEBAGAI UPAYA PENINGKATAN MUTU LULUSAN - Hiryanto Hiryanto (JIV-Jurnal Ilmiah Visi, 2009)
The Government could perform its functions and tasks if it has qualified personnel. To improve its personnelâ€™s competence, the Government has been conducting several kinds of training which have not brought satisfactory results. This research aimed at exploring the possibility of implementing andragogic concept in a training model to improve the training graduatesâ€™ competence. This case study was conduced in The Education and Training Center of Yogyakarta Province and found an andragogy-based training model with detailed steps. Anticipating some hindrances that could be faced by the trainers in implementiation of this model, this research recommended some alternative solutions.